A Secure Relay Protocol for Door Access Control - Wognsen, Erik Ramsgaard; Karlsen, Henrik Søndberg; Calverley, Marcus; Follin, Mikkel Normann; Thompsen, Bent; Hüttel, Hans (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2012: Anais do XII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2012)
Physical keys are easy to use but difficult to manage securely for large institutions. Digital replacements have been created, but dedicated hardware such as smartcards or RFID tags can have the same problems as physical keys. Several commercial products try to solve this by using the users' Bluetooth-enabled mobile devices as keys, but the built-in security of the Bluetooth standard is insufficient. Furthermore, to manage a varying set of users, such systems may require the door locks to be connected to the Internet which may require expensive infrastructure. We present a cryptographic protocol and a prototype implementation that solves these problems by letting door locks communicate with a central server using the Internet connections of the users' mobile devices. The protocol is specified formally in the applied π-calculus and security through secrecy and authenticity is verified using the cryptographic protocol verifier ProVerif. A prototype of the system is implemented for Android smartphones.